A preliminary report on the aerodynamic characteristics of a 40 degrees swept back wing of aspect ratio 4.5 - Barna, P. S. (College of Aeronautics, 1957)
Experimental investigations have been made of the now characteristics on wings of moderate sweepback. This note presents the results of the experimental investigation into the pressure distribution over a swept back wing, having an aspect ratio 4. 5 and sweep back angle 40° at quarter chord. A half model technique has been used. The wing section was R. A. E. 101 (symmetrical) with 6% maximum thickness and zero camber. Measurements of chordwise pressure distributions at a number of spanwise sections were made in the incidence range 2 - 32°. The experiments were performed at Reynolds numbers of 0. 9 x 10(6) and 2 x 10(6) (based on geometric mean chord). From these measurements, lift, drag and pitching moment characteristics of the wing were calculated.